(untitled) (Modern American Journal of Engineering, Technology, and Innovation, 2025)
This paper reviews the structure and function of saw ginning machines and fiber cleaners, focusing on models like 4DP-130 and 8DP-90. It presents technical improvements that enhance fiber quality and ginning efficiency.